Multiple Infections in Pacific White Shrimp (Penaeus vannamei) with Black Gill Disease - A.Uma; G.Rebecca; P.Karthik; S.Gangatharan; S.Ganesh Babu (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Penaeus vannamei (Pacific white shrimp) is the most extensively farmed among the crustaceans globally. Disease is the major impeding factor in the commercial culture of P vannamei undertaken in freshwater, brackish and marine aquaculture systems. In this study, P. vannamei samples were collected from a commercial shrimp farm at Tiruvallur district, Tamilnadu that has reported black gill disease. The clinical symptoms observed in the shrimp were melanized black gills, reduced feeding, surfacing and mortality in the early morning. Samples of gills were collected aspectically and diagnosed for bacterial Acute Hepatopancreatic Necrosis Disease (AHPND); viral diseases viz., Gill Associated Virus (GAV), White Spot Syndrome Virus (WSSV), Yellow Head Virus (YHV), Infectious Hypodermal and Hematopoietic Necrosis Virus (IHHNV) and fungal infections by conventional diagnostic methods and PCR following confirmation by nucleotide sequencing. The results of the study showed that P. vannamei infected with black gill disease had multiple infections with fungus, Aspergillus niger and virus WSSV.